The Role of Controlled Motivation in the Self-Esteem of Adolescent Students in Physical Education Classes - Alfonso Valero-Valenzuela (MDPI AG, 2021)
The aim of this cross-sectional study was to analyse the relationships between the satisfaction of psychological basic needs, physical education, academic controlling motivation, and self-esteem, and to propose a prediction model in line with the postulates from the hierarchical model found in the self-determination theory. The participants were 618 physical education students from primary and secondary school (317 girls and 301 boys) aged between 10 and 14 years old (M = 11.62; SD = 0.94). The questionnaires basic psychological needs in exercise measurement scale (BPNES), perceived locus of causality scale (PLOC), the academic motivation scale (EME), and physical self-perception profile (PSPP) were used to measure the studied variables. The results showed that autonomy and relatedness significantly and negatively predicted physical education controlling motivation, which predicted a positive and significant academic controlling motivation. This, in turn, negatively and significantly predicted self-esteem. It is concluded that it is essential to avoid controlling motivation to promote the development of a positive self-perception in students.